The Relevance Of The Philosophy Of Karl Marx In A Modern State - DUROTOLU, OLUSEGUN (Journal of Posthumanism, 2024)
In a world of misrule, oppression, marginalisation by the rich, unemployment coupled with dictatorial tendencies of the ruling class, where the majority of the population is living under penury with the rich and those in the position of leadership living opulence lifestyle, building oasis of luxuries in deserts of wants, two political-economic ideologies are out for a competition to correct these anomalies. The two most prominent social, political, and economic ideologies are Capitalism and Socialism. To expose the wickedness inherent in capitalist-oriented economies, Karl Marx wrote about his philosophy and jurisprudential thoughts, which are now known as Marxist Legal Theory. The key points of division between the two are that capitalism connotes private ownership of the means of production, while Socialism connotes government ownership of the means of production. When communism advances from Socialism, it connotes a classless society that sheds itself of the remnants of its capitalist features. The writings of Karl Marx and his disciples, such as Lenin, Kautsky, and Hilferding, positioned Communism above Capitalism. This writing makes Communism one of the most influential economic theories of all time. Most writing centres on the key to understanding how Capitalism and Communism have influenced the War exploits and competition between the two superpowers of the United States of America and the defunct Soviet Union, the culmination of this ideological competition being catastrophic wars in Korea and Afghanistan, fought along ideological lines. The essential features of Marxian philosophy, as a derivative of Hegelian Metaphysics, the influence of Capitalism and Communism in the quest for empires through colonialism, and the creation of political alliances along these ideological lines are the focus of this paper. Meanwhile, there are few writings on the relevance and failures of Marxist philosophy and the lessons for societies. It is, therefore, the intention of this paper to also discuss the above hiatuses. This paper illuminates the origins of Marxism, critiques Marxism, explores the relevance of Marxian jurisprudential thought, and draws lessons for modern societies.